Bridged and fused triazolic energetic frameworks with an azo building block towards thermally stable and applicable propellant ingredients. Issue 44 (5th November 2021) - Yu, Qiong; Li, Fengsheng; Yin, Ping; Pang, Siping; Staples, Richard J.; Shreeve, Jean'ne M.
Abstract : Smart assembly of an azo bridge into trinitromethyl triazoles, and controllable azo-trinitromethyl cyclization yield a novel green high-density energetic oxidizer and two fused nitrotriazolones with excellent thermal stabilities. Abstract : The assembly of nitrogen-rich building blocks determines the energy storage capacity and affects the stability of energetic materials. Owing to the environmentally harmful properties of the propellant, ammonium perchlorate (AP), much research has explored halogen-free replacements which often suffer from poor thermal stability. In our goal of balancing performance and stability, we report access to an energetic molecule (3 ) by smart assembly of an azo bridge into trinitromethyl triazoles. Compound 3 exhibits a decomposition temperature of 175 °C, which approaches the highest among reported trinitromethyl derivatives. The density (1.91 g cm −3 ) and oxygen balance (+29%) for 3 exceed other candidates, suggesting it as a high energy dense oxidizer (HEDO) replacement for AP in rocket propellants. One-step azo-involved cyclization of 3 give two fused nitro triazolones, (FNTO ) 4 and its N -oxide 5, having thermal stabilities and energies superior to the analogous derivatives of 5-nitro-2, 4-dihydro-3 H -1, 2, 4-triazole-3-one (NTO ). The comparison of properties of the fused triazolones 4 and 8 and their N -oxide derivatives 5 and 9 shows that formation of an N -oxide is an effective strategy which results in an increase of the decomposition temperature, oxygen balance, specific impulse, and detonation properties and in a decrease of the sensitivity of the corresponding energetic material. This work highlights bridged and fused triazolic energetic frameworks with an azo building block providing an alternative structural motif for seeking an applicable high-energy ingredient.